Does propolis can relief toothache??? - Ardo Sabir (Journal of Dentomaxillofacial Science, 2019)
Objective: The aim of this literature review is to highlights the role and mechanisms of propolis at the molecular level in relief toothache caused by dental pulp inflammation.Methods: This review complied data from our study as well as from other researchers, focusing on molecular mechanism of inflammation, dental pain mechanism caused by inflammation and the role of propolis on inflammatory process.Results: Both in vitro and in vivo or even clinical research revealed thatpropolis has anti-inflammatory. Propolis could suppresses cyclooxygenase(COX) and lipoxygenase (LOX) enzymes during inflammation. COX-2 is mainly inhibited by flavonoid which suppresses prostaglandin endoperoxide synthase at high concentration depending on the hydrophilicity and structure whereas LOX is mainly inhibited by quercetin component of propolis. The major component of propolis is the caffeic acid (3.4-dihydroxycinnamic acid) phenethyl ester (CAPE). It has anti-inflammatory by inhibits LOX and COX enzymes that are involved in the AA metabolism pathways.Conclusion: It could be that propolis effective to relief toothache (odontalgia).